Inpatient rehabilitation can improve functional outcomes of post-intensive care unit COVID-19 patients—a prospective study. Issue 2 (16th January 2023) - Rodrigues, Margarida; Costa, Ana João; Santos, Rui; Diogo, Pedro; Gonçalves, Eugénio; Barroso, Denise; Almeida, Miguel P.; Vaz, Inês Machado; Lima, Ana
Abstract: Purpose: To evaluate the impact of an inpatient multimodal and intensive rehabilitation program on neuromuscular, respiratory, and functional impairments of post-ICU COVID-19 patients. Materials and methods: Prospective study including post-ICU COVID-19 survivors consecutively admitted to a rehabilitation centre. Rehabilitation was conducted by an interdisciplinary team. Medical Research Council (MRC) score, maximum expiratory pressure (MEP), maximum inspiratory pressure (MIP), peak cough flow (PCF), Functional Oral Intake Scale (FOIS), Brief Balance Evaluation Systems Test (Brief-BESTest), Timed Up and Go (TUG) test, 1 min Sit to Stand Test (1′ STST), 6 min Walking Test (6MWT), Fatigue Assessment Scale (FAS), Functional Independence Measure (FIM) were assessed at admission (T0) and discharge (T1). Results: A total of 42 patients were included. After 32.00;26.00 days of inpatient rehabilitation, there was a significant improvement in limb and respiratory muscle strength, cough effectiveness, fatigue, balance, exercise capacity, and in the ability to perform activities of daily living. Advanced age, longer acute care hospitalization, depressive symptoms, and cognitive deficits were associated with poorer functional outcomes. Conclusion: Post-ICU COVID-19 patients present multiple sequelae with detrimental functional impact. An adapted interdisciplinary rehabilitation program is essential for a thorough evaluation of these patients and results in significant functional gains. IMPLICATIONS FOR REHABILITATION: Post-ICU COVID-19 survivors present multiple sequelae and disabilities. An intensive and interdisciplinary inpatient rehabilitation results in significant improvement in limb and respiratory muscle strength, cough effectiveness, fatigue, balance, exercise capacity, and ability to perform activities of daily living. Timely referral from the acute care setting to rehabilitation services is crucial to minimize the functional impact of severe multisystemic disease and prolonged hospitalization.